Physical activity counseling within the «KiKli Fit»-project: Development and first implementation - Julia Schmid; Bianca Schmidli; Lisa Hillebrecht; Christina Schindera; Nicolas von der Weid; Eva Katharina Brack; Valentin Benzing (Bern Open Publishing, 2024)
Introduction Increasing physical activity (PA) levels in children and adolescents with cancer holds promise for enhancing outcomes both during treatment and into survivorship (Stout et al., 2017). Despite this potential, the promotion of PA within Swiss pediatric oncology units remains largely overlooked. To address this gap, the "KiKli Fit" project has been initiated. This program features personalized training sessions during acute care, accompanied by PA counseling during the transition to the post-acute phase. Importantly, it engages not only the patients but also their families, since they play a crucial role in shaping youth's PA behavior (Cheung et al., 2021). The PA counseling is designed to enhance motivation, volition, enjoyment, family health-climate, and ultimately, foster an active lifestyle (Schorno et al., 2022). This study aims to outline the theoretical development of the counseling approach and present initial findings from its implementation. Methods We plan a two-arm multicenter crossover-controlled trial to investigate the effects of the whole PA program. The trial will compare the PA program (intervention group in Bern, n = 40) with standard treatment (control group in Basel, n = 40). Participants will be aged 6-18, newly diagnosed with cancer and undergoing neurotoxic treatment for at least six weeks. The PA counseling comprises four sessions involving the child or adolescent and their parents. These sessions cover various topics, including parental concerns about their child performing PA, individual preferences in exercise and sports, and ways to be physically active as a whole family. Motivational interviewing techniques are applied across all sessions. The study will start in early 2024. Outcomes will be measured three times (once at admission, after twelve weeks of intervention and for follow-up after six months). Discussion The "KiKli Fit"-project is a complex program that aims to promote PA in and after acute care by combining personalized training sessions with PA counseling. The scalability of the PA counseling is a key advantage, allowing it to reach a wide demographic, including those who have completed treatment. Fostering PA in young cancer patients seems to particularly important because it can set a foundation for a healthier lifestyle as they transition into adulthood. References Cheung, A. T., Li, W. H. C., Ho, L. L. K., Chan, G. C. F., & Chung, J. O. K. (2021). Parental perspectives on promoting physical activity for their children surviving cancer: A qualitative study. Patient Education and Counseling, 104(7), 1719-1725. https://doi.org/10.1016/j.pec.2020.11.009 Schorno, N., Gut, V., Conzelmann, A., & Schmid, J. (2022). Effectiveness of individual exercise and sport counseling based on motives and goals: A randomized controlled trial. Journal of Sport and Exercise Psychology, 44(2), 103-115. https://doi.org/10.1123/jsep.2021-0018 Stout, N. L., Baima, J., Swisher, A. K., Winters-Stone, K. M., & Welsh, J. (2017). A systematic review of exercise systematic reviews in the cancer literature (2005-2017). PM&R, 9, 347-384. https://doi.org/10.1016/j.pmrj.2017.07.074